Smash Ability in Volleyball Games Senior High School: The Plyometric Training and Leg Muscle Strength - Suhardiman, Muhammad Akhsan; Hudain, Muh. Adnan; Jamaluddin; Nur, Muhammad; Hasyim (Education and Talent Development Center Indonesia (ETDC Indonesia), 2024)
This research aims to determine the effect of plyometric box jump training on improving smash skills. Plyometric depth jump training enhances smash skills. Differences in the Effect between Box Jump and Depth Jump Training on Improving Smash Skills. This type of research is quasi-experimental using two groups, namely the box jump and depth jump groups, each consisting of 10 MAN 1 Bone students. Data collection techniques use observation, tests, and documentation. The results of the T-test show that the significance value for depth jump training is 0.000 and box jump training is 0.001, indicating that each exercise has an influence. For depth jump training, the increase in smash ability was 4.40, while for box jumps, it was 2.60. Conclusion 1: Plyometric box jump training influences the improvement of Smash skills. 2) Plyometric depth jump training affects improving Smash skills. 3) There is a difference in the influence between box jump and depth jump training, which have different influences on improving smash skills.